Investment crowding-out and labor market effects of financialization in the US - Ignacio González; Hector Sala (Institute for the Study of Labor (IZA), 2013)
This paper studies the impact of financialization on unemployment in the U.S. We estimate a dynamic multi-equation macro labor model including labor demand, labor supply, wage-setting and capital accumulation equations. Financialization appears as a key determinant of capital accumulation which, in turn, is the transmission channel towards its unemployment effects. We conduct a series of counterfactual simulations where we quantify the macroeconomic consequences of the recent swings experienced by the financialization process. We find that it has had relevant unemployment effects in all periods considered, even in those where financial payments were not the main driver of capital accumulation. We also identify a structural change in the financialization process in the early 1980s, and find that it has caused U.S. unemployment to systematically fluctuate around 2 percentage points above what it would otherwise have done. We call for a reappraisal of the way financial markets work, and stress the vital need of preventing financial devices that result in productive investment crowding-out.
Keywords: D2; E22; E24; G2; 330; financialization; capital accumulation; unemployment; chain reaction theory